2021
DOI: 10.1021/acs.energyfuels.1c03223
|View full text |Cite
|
Sign up to set email alerts
|

Review of Developments in Nanotechnology Application for Formation Damage Control

Abstract: Formation damage has the potential to impair and weaken reservoir productivity and injectivity, causing substantial economic losses. Oil and gas wells can be damaged by various mechanisms, such as solid invasion, rock–fluid incompatibilities, fluid–fluid incompatibilities, and phase trapping/blocking, which can reduce natural permeability of oil and gas near the wellbore zone. These can happen during most field operations, including drilling operations, completion, production, stimulation, and enhanced oil rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 179 publications
0
16
0
Order By: Relevance
“…On the one hand, it has been discovered that drilling fluid with nanoparticles has a tiny particle size and a large surface area, which has a promising future. The nanomaterials can effectively seal the pore throat of the reservoir and enhance the stability of the wellbore, thus realizing the role of reservoir protection (Ngata et al, 2022;Zamora-Ledezma et al, 2022). On the other hand, the drilling fluid with polymers has also become one of the most widely used drilling fluid systems after years of development.…”
Section: Locationmentioning
confidence: 99%
“…On the one hand, it has been discovered that drilling fluid with nanoparticles has a tiny particle size and a large surface area, which has a promising future. The nanomaterials can effectively seal the pore throat of the reservoir and enhance the stability of the wellbore, thus realizing the role of reservoir protection (Ngata et al, 2022;Zamora-Ledezma et al, 2022). On the other hand, the drilling fluid with polymers has also become one of the most widely used drilling fluid systems after years of development.…”
Section: Locationmentioning
confidence: 99%
“…1−3 These operations allow foreign fluid to infiltrate the formation, resulting in an interaction between the foreign fluid and the formation fluid or the foreign fluid and the formation rock, which can cause formation damage, lowering well productivity and inflicting significant economic losses. 4,5 To minimize and manage the degree of formation damage in various types of reservoirs, several researchers have conducted experiments and studies regarding formation damage mitigations. 6−9 For many years, formation damage has been regarded as a challenge in the oil and gas industry and has become a focal point of research.…”
Section: Introductionmentioning
confidence: 99%
“…They applied nanotechnology in EOR, water shutoff, dewatering, and improvement of production in heavy oil, and their results were based on the oil production rate. Ngata et al, 5 on the other hand, studied the deployment of nanotechnology in the oil and gas industry to control formation damage. Their research showed that nanotechnology can be applied during drilling, completion, EOR, and stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation damage can impair and reduce reservoir performance and consequently cause substantial economic losses. Formation damage is brought by several mechanisms such as solid invasion, and poor compatibility of either rock and fluid or fluid and fluid (Ngata et al, 2021). Formation damage begins immediately when drilling operations begins and continues during the productive life of the well.…”
Section: Interaction Of Acid and Geothermal Reservoir Formationmentioning
confidence: 99%